2014
DOI: 10.2217/bmt.14.22
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of febrile neutropenia following adjuvant breast chemotherapy with docetaxel, carboplatin and trastuzumab

Abstract: SUMMARY  Aim: To determine the incidence of febrile neutropenia (FN) following adjuvant chemotherapy with docetaxel, carboplatin and trastuzumab (TCH) for early-stage breast cancer and the grade of neutropenia after cycle one. Methods: A retrospective multicenter audit of patients with early-stage breast cancer treated with TCH, was conducted at four Australian hospitals between October 2009 and September 2013. Results: Of 79 patients analyzed, data from 78 women were evaluated for FN incidence and data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Another study found that G-CSFs was being over utilized in patients undergoing chemotherapy associated with low risk of FN and underutilized in patients with high risk of FN. This finding is similar to ours, whereby G-CSFs were underutilized in patients with high risk of FN [17][18][19][20][21][22][23][24][25]. However, G-CSFs were prescribed appropriately in intermediate-and low-risk patients at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…Another study found that G-CSFs was being over utilized in patients undergoing chemotherapy associated with low risk of FN and underutilized in patients with high risk of FN. This finding is similar to ours, whereby G-CSFs were underutilized in patients with high risk of FN [17][18][19][20][21][22][23][24][25]. However, G-CSFs were prescribed appropriately in intermediate-and low-risk patients at our institution.…”
Section: Discussionsupporting
confidence: 89%
“…Both regimens are now classified as high-risk FN regimens in the current guidelines. [13][14][15] FOLFOX has been classified as an intermediate-risk regimen based on clinical trial findings for FOLFOX4. 7,16 FN risk for FOLFOX6, an alternative regimen with a more simplified administration of 5-fluorouracil infusion, 17 remains unclassified.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the US Oncology group reported a 5% FN incidence in patients receiving TC (docetaxel/cyclophosphamide) regimen, while numerous studies using the same regimen have reported a much higher incidence of FN ranging between 25% and 50%, being 29% in a pooled meta‐analysis . Likewise, the incidence of FN among patients treated with TCH has been reported to range from 7.1% to 41.0%, being 9.8% in the BCIRG‐006 trial . Importantly, in this trial, another 11% of TCH‐treated patients developed neutropenic infection, which collectively brings neutropenia‐associated complications to the 20% threshold, proposed for PPG.…”
mentioning
confidence: 74%